Comparison of plethysmographic variability index (PVI)-based versus standard monitoring based fluid therapy in severe traumatic brain injury patients undergoing craniotomies: a randomised controlled trial - Ramanathan, Radha A/P (2020)
Background: Goal directed fluid therapy in imperative in the management of patients with traumatic brain injury. Inadequate resuscitation can worsen secondary brain injury wherelse excessive fluid may worsen cerebral oedema. This study aims to ascertain the use of Plethysmographic Variability Index (PVI), as a guide for targeted therapy based on total fluids used and blood tests, which include lactate, electrolytes, blood gases and renal function. PVI is a non invasive method of dynamic fluid status monitoring, which have been used to varying success in other patient population. This is the first study to assess the utility of PVI in severe traumatic brain injury patient undergoing emergency craniotomies and craniectomies. Methods This is a single blinded randomised control trial. All patients presenting or referred to the emergency department HUSM diagnosed with severe traumatic brain injury , and planned for craniotomies, aged between 18-60 years, were recruited to this study. A total of 68 patient were recruited. The patients were randomly assigned to PVI group and Standard monitoring (SM) group with 34 patients in each group. The primary outcome of this study aims to assess if PVI-based goal directed fluid therapy show a reduction in amount of fluid used. The secondary outcomes reduction in postoperative lactate, no significant increase in electrolyte (sodium and chloride) levels, reduction in serum creatinine and improvement of blood gases in term of pH and BE as compared to conventional fluid therapy. After induction with standard anaesthesia procedure, all patients were monitored with the electrocardiogram (ECG), Non Invasive Blood Pressure (NIBP), Pulse oximetry (SpO2) and invasively with the arterial line and central venous line as per stanadrard protocol for craniotomies in our institution Patients in the PVI group were given the Massimo Pulse Oximetry to measure PVI from induction ( 0 H) until 24 hours (24 H) in the ICU. All patient were subjected to maintenance fluid regime according to Holliday- Segar . In conventional group, if the mean arterial pressure (MAP) < 70mmHg or heart rate (HR) ≥ 100 bpm , patient were given crystalloids (Sodium Chloride 0.9% or a balanced solution such as Stereofundin) up to 20mls/kg, subsequently 250mls of Gelafundin and Noradrenaline infusion or packed cell transfusion if Hb levels < 10g/dL. In the PVI group, PVI ≥ 13 indicates hypovolemia. These patient were given up to 20 mls/kg of crystalloids , followed by Gelafundin 250 mls and packed cell transfusion if Hb was < 10g/dL , until PVI .< 13% . A PVI of < 13% indicated adequate volume. However in these patient with a PVI of < 13% and MAP <70 mmHg or HR ≥ 100 bpm, Noradrenaline infusion was initiated . Fluid management protocols in the Intensive Care Unit included urine output, with recommended intervention at a urine output of less than 0.5-1cc/kg/hr. The hemodynamic data and total fluid administered, and laboratory parameters (serum lactate, sodium (Na), chloride (Cl), pH, base excess (BE), creatinine) at 0 H and 24 H was recorded. The demographic data in between groups were analysed using descriptive analysis chi square test. Independent t-test was used to analyze the amount of different types of fluids used, total amount of fluid used and blood loss. The difference in lactate, pH, BE, Na+ and Cl- and creatinine between groups was analysed using the Independent t-test. Results Demographic features of both the conventional and PVI group were similar in terms of age (mean age of 32 years) , sex (predominantly male) , types of surgery , GCS (Glasgow coma score), SAPS scores, Marshal and Rotterdam CT scoring. The primary outcome evaluation revealed that PVI group showed no significant difference in term of total fluid used as compared to the conventional group [6352.72(2134.82) vs 5917.50(2171.42); p 0.422]. In addition , there were no significant difference in individual fluid types and blood component administered between both groups. Analysis of the secondary outcomes showed that here was no significant difference in pre lactate levels PVI and conventional [2.37(1.74-3.00) and 3.13(2.58- 3.67); p 0.069] and 24 H lactate levels [1.42(1.16-1.68) and 1.75(1.39-2.11) ;p 0.135] .There were no significant differences in pre and post serum sodium, chloride and creatinine levels between PVI and conventional group. There were no significant differences in pH and BE levels at 0 H between PVI and conventional group. There was a significant difference in 24 H pH levels between PVI and conventional [7.38(7.35 – 7.40) and 7.41(7.39-7.42); p 0.030] and 24 H BE [-1.81 (-2.97 to -0.65) and 0.41(-0.71 to 1.54); p< 0.007], however in both groups remain within the normal safe range of pH and BE. Conclusion In summary, PVI guided fluid therapy is not associated with a significant reduction in amount and type of fluid used. PVI confers no clinically significant benefit to conventional therapy in terms of lactate, sodium, chloride, pH, BE and creatinine levels.